Emotional Intelligence and Personality in Students Pursuing Professional and Non-Professional Courses - The Influence of Personal Correlates - Archana Das, G. M. (Prabandhan: Indian Journal of Management, 2011)
The concept of emotional intelligence is very important as it is directly related to success and enduring performance in any setting, be it in an educational field in terms of scoring better grades or in an organisation by maintaining good relations with people and thereby earning brownie points from the superior and reaching the corporate ladder very soon. The present study examines the influence of gender (male=139, female=107) on emotional intelligence and personality among professional (168) and non-professional students (78). Emotional intelligence scale developed by Dr.Meera Shanker and Dr.Omer Bin Sayeed (2006) was used to examine the emotional intelligence of students. Myer Briggs Type Indicator Form G developed by Isabel Myers and Katherine Briggs (1977) was used to measure the personality preference on 4 dichotomies that include Extraversion vs. Introversion, Sensing vs. Intuition, Thinking vs. Feeling, and Judging vs. Perceiving. Results indicate that female non-professional students are better, emotionally intelligent than male non-professional students. Implications of the study and suggestions for future research are mentioned. Keywords: Emotional intelligence, personality, professionals, non-professionals, gender.